A study on perception of Malaysian citizen towards Islamic banking in Malaysia / Nurul Ain Abdul Manan - Abdul Manan, Nurul Ain (2017)
This research attempted to investigate the perception of Malaysian citizen towards Islamic Banking in Malaysia. The research conducted by questionnaire method as the Primary Data which the data for the research were collected through a questionnaire survey of Malaysian citizen in Kuala Lumpur area. In this research, 200 respondents were carried out as a sample of Malaysian citizen. In this research, Perception of Malaysian citizen is a dependent variable and awareness, understanding and demographic factor are independent variable. The result of analysis will be obtained through research using SPSS for interpreting data, Microsoft Excel to combine data. Besides that, Google use to search supporting document or related journal, article which is secondary data to support this research. So that it can be concluded that one out of three independent variables have significant relationship between dependent variable which is Malaysian perception toward Islamic banking and independents variable which is awareness, understanding and demographic factors.